ADVANCED OXIDATION PROCESSES (AOX) TEXTILE WASTEWATER - Salas C., G. (2010)
Advanced Oxidation Processes (AOX) are based on the in situ generation of hydroxyradicals (·OH), which have a high oxidation potential. In the case of Fenton processes !he generation of hydroxy radicals takes place by the combination of an oxidation agent (H202) with a catalyst (Fe(II)). These radicals are not selective and they react very fast with the organic matter,being able to oxidize a high variety of organic compounds. This property allows the degradation of pollutants into more biodegradable compounds, and,in some cases, their complete mineralization into C02 and mineral acids. Under optimal conditions, (pH=3, (Fe 2+] = 200 mg/L, [H2O2] = 3612 mg/L) the Fenton processes are able to reduce !he concentration of the organic matter present in the textile effiuent, up lo 97%.